Myocardial Infarction-Associated Shock: A Comprehensive Analysis of Phenotypes, SCAI Classification, and Outcome Assessment - Stanislav Dil; Maria Kercheva; Oleg Panteleev; Sergey Demianov; Aleksandr Kanev; Nina Belich; Boris Kornienko; Vyacheslav Ryabov (Medicina)
Background and Objectives: In-hospital mortality associated with myocardial infarction complicated by cardiogenic shock (MI-CS) remains critically high. A particularly challenging form, mixed shock (MS), combines features of cardiogenic shock (CS) with distributive elements such as vasodilation and reduced vascular resistance. MS is associated with elevated mortality rates and presents unique diagnostic and therapeutic challenges. This study aimed to analyze the clinical, historical, instrumental, and laboratory characteristics of the primary phenotypes of MI-CS, stratified according to the Society for Cardiovascular Angiography and Interventions (SCAI) shock severity scale. Materials and Methods: In this single-center, retrospective observational study, we reviewed the medical records of 1289 patients admitted to the emergency cardiology department from 1 January to 12 December 2020. Among them, 117 patients were identified as having MI-CS and were divided into two groups: MS (n = 48) and isolated CS (n = 69). The data were analyzed using the SCAI shock classification. Logistic regression analysis was employed to identify predictors of mortality and improved survival outcomes. Results: Patients with MS were older (80 years [71.0; 83.0] vs. 73 years [64.0; 81.0], p = 0.035). The overall mortality rate was significantly higher in the MS group (68% vs. 53%, RR = 1.438, 95% CI: 1.041–1.986, p = 0.03). Logistic regression identified mechanical ventilation (OR = 8.33, 95% CI: 2.54–22.80, p = 0.012), elevated lactate levels (OR = 1.20, 95% CI: 1.02–1.41, p = 0.026), and cardiopulmonary resuscitation (CPR) (OR = 7.97, 95% CI: 2.51–24.40, p < 0.0001) as independent predictors of mortality. Conversely, the use of an intra-aortic balloon pump (IABP) (OR = 0.22, 95% CI: 0.06–0.80, p = 0.021) and a higher body mass index (BMI) (OR = 0.91, 95% CI: 0.84–0.99, p = 0.038) were associated with reduced mortality risk. Conclusions: MS in the context of MI-CS represents a distinct clinical phenotype with specific hemodynamic features and significantly worsened outcomes. The identification of mortality predictors, such as mechanical ventilation, elevated lactate levels, and CPR, alongside protective factors like IABP use and a higher BMI, underscores the importance of early and tailored therapeutic interventions. These findings highlight the need for further studies to refine treatment protocols and improve outcomes in this high-risk population.